Diversity and distribution of Udotea genus J.V. Lamouroux (Chlorophyta, Udoteaceae) in the Yucatan peninsula littoral, Mexico - Acosta-Calderon, Julio Adulfo; Hernández-Rodríguez, César; Mendoza-González, Ángela Catalina; Mateo-Cid, Luz Elena (Phytotaxa, 2018)
A survey of the diversity, distribution, and taxonomy of the genus Udotea from the Yucatan peninsula littoral, Mexico, is presented. The results are based on a review of herbarium specimens, bibliographic data, and collections made by the authors during 2012–2016 at 34 localities along the study area. Macro and microscopic characteristics, relevant photographs, and descriptions are provided for each taxon. A total of 17 taxa of Udotea were recognized. One new record is cited for Quintana Roo, two for Yucatan, and five for Campeche coasts. The Quintana Roo littoral presents the highest number of Udotea species (17), followed by Campeche (13), and finally Yucatan (9). The Udotea taxa could be segregate by the presence of lateral appendages in the blade siphons and, the shape of the lateral appendages of the blade and stipe siphons.